pНРМА-hydrogel does not improve intensive autogenic recovery of motor function after lateral spinal cord fragment excision in adult rats - Sahaidak, Victor; Medvediev, Volodymyr (The Ukrainian Scientific Medical Youth Journal, 2026)
: spinal cord injury (SCI) is a form of trauma with high prevalence, mortality, and disability. One approach in SCI rehabilitation is to create conditions for regenerative axon growth across the lesion site using tissue scaffolds. notably pHPMA-hydrogel (pHPMA — poly(N-[2-hydroxypropyl] methacrylamide)). Assessing the effectiveness of such approach can only be done in laceration models of SCI with reliable reproducibility. The aim of this work was to determine the effect of immediate implantation of pHPMA-hydrogel into the epicenter of a unilateral one-millimeter spinal cord defect in an adult rat on the paretic limb motor function in comparison with the effectiveness of the same intervention in young animals. The study was performed on white male outbred adult rats (3–4 months). For comparative analysis of the obtained data, the results of young animals from another institution, previously published in other works, were used. In both cases, a 1-mm excision of the spinal cord lateral half at the lower thoracic/upper lumbar level was maded, with immediate filling of the defect by a fragment of pHPMA-hydrogel. Over a period of 5 months after intervention, the motor function of the paretic limb in adult animals reached about one-third of normal levels, both with and without pHPMA-hydrogel implantation. Spasticity of the paretic limb was minimal in adult animals with or without hydrogel implantation. There is generally a negative correlation between motor function and spacticity. These data suggest that pHPMA-hydrogel implantation into a one-millimeter unilateral spinal cord defect, unlike in young animals, does not significantly affect recovery outcomes in adult animals. Based on a comparative analysis of the results of young and adult animals we hypothesize that the recovery of the paretic limb’s motor function after unilateral SCI may be mediated with the participation of interneurons/propriospinal neurons in the contralateral part of the injured cord with a limited rostro-caudal axonal and dendritic extent.